PENGARUH KEMAMPUAN, LINGKUNGAN KERJA, KOMITMEN ORGANISASI DAN SIKAP KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN BARAT - Menawastuny Munthe (Manajemen dan Bisnis, 2020)
The problem in this research is: How does the ability to influence employee performance at the West Medan Pratama Tax Office. How does the influence of the work environment on employee performance. How does the influence of organizational commitment on employee performance on, How does the influence of work attitudes on employee performance, How does the influence of ability, work environment, organizational commitment and work attitude on employee performance at the West Medan Pratama Tax Office.The hypothesis proposed is: Ability to have a positive and significant effect on employee performance at the West Medan Pratama Tax Office, Work environment has a positive and not significant effect on employee performance, organizational commitment has a positive and not significant effect on employee performance, work attitude has a positive and significant effect on employee performance, ability, work environment, organizational commitment and work attitude have a positive and significant effect on employee performance at the West Medan Pratama Tax Office. The study was conducted at the West Medan Pratama Tax Office. Jalan Dormitory No. 7-A, Medan-20151 with 96 research samples. Based on the analysis results obtained there is a significant effect between work ability on the performance of West Medan Pratama Tax Office employee, because according to the results of the analysis of t count t-table (1.735 1.66) at n = 96 with a significance level of 95%, There is an influence Significant between the work environment on employee performance analysis results t count t-table (2.687 1.66) at n = 96 with a significance level of 95%, There is a significant influence between organizational commitment to employee performance because according to the results of t analysis t-table (4.335 1.66) at n = 96 with a significance level of 95%. There is a significant influence between work attitudes on employee performance, because according to the results of the analysis of tcount t-table (2.027 1.66) at n = 96 with a significance level of 95%. F-count value F table (39,988 2.48 ) with the numerator dk 4 and the denominator 91 together (multiple) there is a positive and significant effect on ability, work environment, organizational commitment and work attitude on the performance of the employees of the West Medan Pratama Tax Office. Thus the hypothesis proposed is accepted.